(untitled) (Journal of Hama University, 2021)
This study is based on demonstrating the impact of Chinese foreign trade of digital goods, both exported and imported, on economic growth rates during the period (2005-2019). By using the auto-regression method for distributed slower “ARDL” after making sure that the time series achieved acceptable stability. The study concluded that there is a significant impact of digital merchandise exports in China on the growth rate of Chinese GDP, and there is a causal relationship from Chinese digital merchandise exports toward the growth rate of Chinese GDP, according to Granger’s causality. There is also a significant effect of imports of Chinese digital goods on the growth rate of Chinese GDP, and there is no causal relationship between imports of Chinese digital goods toward the rate of Chinese economic growth during the study period, according to Granger’s causality.